Construction of gender and identity in Genesis: the subject and the other - Matskevich, Karalina (Library of Hebrew bible/Old Testament studies, 2019)
Intro -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgements -- List of Abbreviations -- Introduction -- Chapter 1: The Subject and Knowledge in Genesis 2-3 -- Defining the Problem -- The Overture: To Eat or Not to Eat -- Yahweh and the Institution of Gender (Gen. 2.18-22) -- hā'ādām and the Interpretation of Gender (Gen. 2.23-24) -- The Human Beings and Knowledge (Gen. 2.25-3.7) -- The Subject on Trial (Gen. 3.8-13) -- The Final Balance: Judgement and Expulsion (Gen. 3.14-24) -- The Two Plots of Yahweh Elohim -- Chapter 2: The Subject and the Land in the Abraham Cycle (Gen. 11.27-25.18) -- The Patriarchal and Matriarchal Successions -- The Call of Abraham: Ambiguities of Election -- The Land as Own and Foreign -- The Gendering of the Land -- The Wife-Sister Ruse: The Subject in Search of Fertility -- The Separation of Abraham and Lot -- 'There Is No Man in the Land' -- Sarah, Hagar and the Project of Dominance (Genesis 16) -- Hagar and Ishmael: Expelling the Other (Genesis 21) -- Final Observations -- Chapter 3: The Mothers and the Mother's Land in the Jacob Narrative (Gen. 25.19-37.1) -- Binary Structures in the Jacob Narrative -- Father's Land vs. Mother's Land -- Rebekah's Plot -- Rachel, Leah and the Twists of God -- The dûdā'îm of Reuben -- The Father's Gods and the Way of Women -- Forms of Binary Relationships in the Jacob Narrative -- Conclusion -- Binliography -- Index of Authors -- Index of Biblical References